Osseous Metaplasia un Ovarian Endometrial Cyst: A Case Report - Asani, Learta; Nikolova, Dafina; Madzunkova, Katerina; Karanfilovski, Vlatko; Pandilov, Stefan; Janevska, V (My University, 2019)
Osseous metaplasia in the female genital tract is a rare condition with unknown clinical importance and unknown etiology. We report a rare case of osseous metaplasia in an ovarian endometrial cyst, and comment to a chronic inflammation as a possible etiology
Keywords: Osseous metaplasia; Ovarian endometrial cyst; Chronic inflammation